EVALUASI DAN DESAIN SISTEM INFORMASI AKUNTANSI PEMUNGUTAN DAN PENYETORAN PPN DALAM UPAYA MENINGKATKAN EFISIENSI KINERJA SUBDINAS PERPAJAKAN PADA PT. PELABUHAN INDONESIA III (PERSERO) CABANG TANJUNG PERAK - Wardhani, Anindya Retno; Utama, A.A Gde Satia (Universitas Airlangga, 2016)
Branch of PT Pelabuhan Indonesia III (Persero) in Tanjung Perak is one of theinstitution body that appointed by the Government to carry out the collection andremittance of WAPU VAT according to PMK No. 85 / PMK.03 / 2012 (amended byPMK No. 136/ PMK.03 / 2012). WAPU VAT collection and deposit system areinefficient because it requires a lot of time and effort when it comes to input the dataentry of tax invoice, printing Tax Deposit and sent it to Bank Perception. Threesteps activities need tobe done more than once. Therefore, Branch of PT PelabuhanIndonesia III (Persero) in Tanjung Perak need the collection and remittance of theWAPU VAT system that sufficient to improve the efficiency of tax subofficesperformance.This research aims to design the accounting information system forcollecting and depositing process WAPU VAT. WAPU VAT Deposit using e-taxpayment application are expected to overcome the problems that will arise in theWAPU VAT system deposit.Exploratory qualitative approach withcase studymethod chosen in order to dig up the real problem occurs and find a solution. Thisresearch are expected to contribute significantly towards Branch of PT PelabuhanIndonesia III (Persero) in Tanjung Perak as a research subject. In addition, theimplementation of draft e-tax application payment system are expected to improveefficiency process of collection and remittance of WAPUVAT.